The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1177/0192513x04272398
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of First Marriage

Abstract: Using survey data from a nationally representative sample, this article explores how marriage timing varies across major religious denominations. Survival analysis indicates that net of statistical controls, Catholics, moderate Protestants, conservative Protestants, and Mormons marry significantly earlier than their unaffiliated counterparts. This holds true for women and men. However, no statistical differences emerge between Jews, liberal Protestants, and the unaffiliated. As surmised, auxiliary statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 78 publications
(123 reference statements)
0
24
0
Order By: Relevance
“…Early evidence revealed that those claiming a religious affiliation are more likely to marry than are the religiously unaffiliated (Heaton and Goodman 1985). And where marriage timing is concerned, conservative Protestants and Latter-day Saints (Mormons) marry, on average, at the youngest ages (Xu et al 2005). Other, less culturally distinctive religious groups are more likely to postpone marriage at rates akin to those in the general population.…”
Section: Correlates Of Remarriage and The Case For Religious Influencementioning
confidence: 99%
See 3 more Smart Citations
“…Early evidence revealed that those claiming a religious affiliation are more likely to marry than are the religiously unaffiliated (Heaton and Goodman 1985). And where marriage timing is concerned, conservative Protestants and Latter-day Saints (Mormons) marry, on average, at the youngest ages (Xu et al 2005). Other, less culturally distinctive religious groups are more likely to postpone marriage at rates akin to those in the general population.…”
Section: Correlates Of Remarriage and The Case For Religious Influencementioning
confidence: 99%
“…Given signs of intergenerational decline in Americans' religiosity (e.g., attendance) (Schwadel 2011), what influence, if any, does religion exert in remarriage timing among young Americans who have recently experienced a divorce? And, if religion does influence remarriage trajectories, are variations among denominational subcultures evident similar to those observed in the timing of first marriage (Rendon et al 2014;Uecker 2014;Xu et al 2005)? In addition, what role, if any, does religious and spiritual capital play in the timing of remarriage? It is possible, for example, that integration within religious networks through regular worship service attendance could serve as a remarriage market among persons of faith.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Individuals that grow up in evangelical denominations continue to attain lower levels of education than other whites, resulting in somewhat lower levels of education among white evangelicals as a whole [61]. In addition, marriage, childbearing, and homeownership tend to occur earlier for evangelical Protestants than for other groups [62][63][64]. Significantly, scholars have suggested that homeowners or those with children in the home hold a greater stake in their neighborhoods and may have particular preferences about neighborhood composition and quality [13,59].…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%